Sosialisasi dan Penyuluhan Ekonomi Islam Pada Karyawan BPR Syariah Dalam Naungan ASBISINDO Pada Masa Pandemi Covid-19 - Tatik Mariyanti; Hermi Hermi; M. Hadi Nugraha (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2022)
The purpose of the research based on PKM activities carried out by the Faculty of Economics and Business, Trisakti University is to increase the understanding of Islamic economics among BPRS employees under the auspices of ASBISINDO. The method used is a qualitative method by conducting surveys and direct observations by conducting counseling and presentations with interactions between speakers and participants, so that a large understanding of Islamic economics can be analyzed for the participants who are almost entirely employees of the BPRS during the covid-19 pandemic. The results of this research on PKM activities are that the understanding of Islamic economics for BPRS employees is getting better, marked by discussion interactions and being able to answer questions from BPRS employee participants. The implementation of this PKM research activity should continue to be carried out periodically and also speakers from the government and the practitioners, so that the results of this research based on PKM research activity can be immediately implemented by the government and practitioners.